Perancangan Sistem Antrian Berbasis Web Dengan Metode Waterfall Pada KPP Samarinda Ilir - Argi Nur Faturrohman; Abdul Rahim (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
This research is intended to be able to apply the Waterfall method in developing a website-based queuing system at the Pratama Tax Office (KPP) Samarinda Ilir. With a primary focus on improving efficiency and customer experience, this study conducted additional evaluation through Black Box testing. This method systematically tests system functionality from the user side. The stages of requirements analysis, design, implementation, Black Box testing, and maintenance, ensure the development of a structured and scalable system. The results are expected to provide effective solutions in modernizing the queuing system, improving services, and meeting needs at the tax office.